SYNTHESIS POLYMER MATRIX COMPOSITE EPOXY FeNdB-Cu FOR RADAR ABSORBER COATING APPLICATION - Sri Mulyati Latifah; Djoko Hadi Prajitno; Muhammad Fadhil Syukron (Jurnal Sains Materi Indonesia, 2021)
SYNTHESIS POLYMER MATRIX COMPOSITE EPOXY FeNdB-Cu FOR RADAR ABSORBER COATING APPLICATION. Radar (Radio Detection and Ranging) is a technology using the principle of electromagnetic for detecting, measuring, and mapping target coordinates. So stealth technology was created to tackle these threats, one of which is the radar absorber coating method (RAC). This research aims to identify the effect addition of Cu to Fe-Nd-B radar absorber material as polymer matrix composite (PMC). The processes were done by powder metallurgy method, started by milling and mechanical alloying process using planetary ball mill for 60 minutes 1000 rpm, 25 kg/mm2 of compaction load, and sintering at the temperature 1000 oC for 3 hours. The coating process was carried out conventional method as much as 1 layer, the variation of resin and magnetic powder are (95:5), (90:10), and (85:5) with the addition of Cu 1%wt. Based on the characterization the lowest RL was obtained at the composition (85:15) with the value 32.08 dB at the frequency of 10.36 GHz, magnetic characterization after doping addition coercivity 0.096 kOe and Saturation 5.22 kG. PMC hardness was raising following to addition of magnetic powder with the 29.2 HD Shore D, and adhesivity value was decreased following to addition of magnetic powder to 0.5 MPa.